Padrões globais do nicho alimentar de lagartos - Cavalcanti, Lucas Barbosa de Queiroga (2018)
The understanding of how both recent and historical factors can mold species ecological traits is crucial for elucidating ecological and evolutionary processes. Compiling a global dataset of dietary aspects of 722 populations of 323 lizard species (across 32 families), we tested the influence of phylogeny on dietary preferences of lizards in a worldwide scale, as well as its relationship with climate, foraging mode, habitat, distribution (tropical/temperate) and body size. Phylogenetic history was the major factor defining dietary preferences on lizards, accounting for 53.79% of total variation. We also found significant phylogenetic signal in prey ingestion on both univariate and multivariate analysis. Iguanian lizards eat more beetles and hymenopterans than noniguanians. We suggest that iguanians evolved traits that facilitate the ingestion of these preys, while non-iguanians does not have these traits and tend to avoid them. Iguanians also seems to have adaptations that facilitate the development of strict herbivory. Noniguanians lizards are usually from two groups: (1) those that feed on termites (especially desert species) or (2) feed on other energetic prey items (such as orthopterans, spiders and roaches). Also, we found evidence for significant climatic influence in dietary preferences, with litter fauna arthropods being more often found on the diet of lizards inhabiting wet/warmer climates. Cold resistant arthropods (beetles and millipedes) were also more ingested in colder climates. Termite ingestion (together with mites and mantids) was associated to seasonal warmer seasonal environments, such as deserts and arid areas, thus providing abundant food source on harsh environments. Herbivory was associated to seasonal environments, probably as an alternative source of food and water. Foraging mode was not a good predictor of dietary preferences, as they were only related to solpugids and mites (~ 3%), neither being primary prey categories. Habitat 4 specialization also seems to predict specific secondary preys, especially on arboreal and semi-aquatic lizard species. Tropical lizards seems to ingest a wide variety of arthropods, while squamates are more ingested by temperate lizard species (probably due to the presence of larger body-sized lizards on temperate zones. Body size was positively correlated to larger prey groups (more energetic efficient) and herbivory (alternative food source and better plant digestion). We support the previous hypothesis that lizard species diet is mostly predicted by evolutionary history, providing interpretations for these patterns and highlighting the importance of other ecological traits as well as environmental variables also modulating the ingestion of both principal and secondary preys among lizard clades.